Human islet separation utilizing a closed automated purification system. - Friberg, A; Ståhle, M; Brandhorst, H; Korsgren, O; Brandhorst, D (2008)
A central step within the human islet isolation process is the separation of islets from contaminating exocrine tissue utilizing linear, continuous density gradients manufactured by means of manually controlled standard gradient makers (SGM). The present study was performed to develop a closed, automated purification system (APS) that customizes density gradient profiles aiming to standardize and optimize human islet purification. Digested human pancreata were pooled, split evenly, and incubated in UW solution according to our standard protocol (n = 11). Continuous density gradient centrifugation was performed in parallel in two refrigerated COBE 2991 cell separators loaded with light (1.076 g/ml) and heavy (1.097 g/ml) Ficoll utilizing either an SGM or two computer-controlled pumps connected to Ficoll-containing bags. Quality control included islet equivalent (IE) yield, purity, in vitro function, and islet cytokine expression. Gradient profiles demonstrated that the APS readily customizes linear and nonlinear gradients. In comparison to the SGM, the APS recovered a higher percentage of the expected volume of continuous gradients (90.0 +/- 1.1% vs. 98.2 +/- 2.0%, p < 0.05). Islet yield (120,468 +/- 15,970 vs. 114,570 +/- 15,313 IE, NS) and purity (51.7 +/- 4.8% vs. 54.4 +/- 4.9%, NS) were nearly identical utilizing the SGM or APS. Decreased MCP-1, IL-6, and IL-8 expression indicated that APS-purified islets were possibly exposed to less proinflammatory stress. Compared to standard procedures, similar success and gentle continuous density gradient separation of human islets is feasible utilizing the APS. The APS facilitates the standardization of this complex procedure according to cGMP standards.